The Effect of Account Receivable Management on Financial Performance of an Organization: A Case Study of Case Hospital Kampala - Jocelyn Kuteesa (My University, 2024)
The overall purpose of this research study is to evaluate the impact of accounts receivable management in an organization with emphasis on Case Hospital Kampala. The research study highlights the current accounts receivable practices used at Case Hospital Kampala, how management of accounts receivable affects financial performance and the enhancement of technology under accounts receivable management.